2010
DOI: 10.1007/s00405-010-1336-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the outcome of idiopathic sudden sensorineural hearing loss treated with hyperbaric oxygen therapy

Abstract: Idiopathic sudden sensorineural hearing loss (ISSNHL) is an otologic emergency with an incidence of about 5-20 per 100,000 of the population per year. There is no universally accepted standard protocol for the treatment of patients with ISSNHL. Hyperbaric oxygen therapy (HBOT), was first reported to improve the outcome following acute inner ear disorders during the late 1960s by both French and German authors. The increase in perilymph oxygenation produced by HBOT provides logical basis for the use of this tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 22 publications
2
42
0
6
Order By: Relevance
“…In a study of 80 patients undergoing HBOT for SSNHL, 5 (6.25%) had ear or sinus barotrauma. 177 In addition, patients may suffer from some degree of confinement anxiety while undergoing HBOT. 175,177 Finally, HBOT is an expensive and time-consuming intervention.…”
Section: Supporting Textmentioning
confidence: 99%
“…In a study of 80 patients undergoing HBOT for SSNHL, 5 (6.25%) had ear or sinus barotrauma. 177 In addition, patients may suffer from some degree of confinement anxiety while undergoing HBOT. 175,177 Finally, HBOT is an expensive and time-consuming intervention.…”
Section: Supporting Textmentioning
confidence: 99%
“…17 Factors identified as improving the outcome of hyperbaric oxygen therapy include early use of therapy, greater numbers of sessions, adjuvant steroid usage, profound hearing loss and low frequency hearing loss. 2,18 The use of hyperbaric oxygen therapy to treat sudden hearing loss in large vestibular aqueduct syndrome patients has been previously reported only twice, with both papers originating from Japan. The original case report involved a 14-year-old girl with acute, right-sided hearing loss.…”
Section: Discussionmentioning
confidence: 97%
“…[10,13,14] The results of salvage HBO therapy in previous studies are demonstrated in Table 4. [9,[14][15][16][17][18] To date, no reports have been published about the hearing outcomes of salvage HBO therapy after combined steroid treatment. The results of this study indicate that there is still something to do after combined steroid treatment in ISSNHL.…”
Section: Discussionmentioning
confidence: 99%